(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Aqueous formulation of rhizopheric beneficial bacteria viz. Bacillus subtilis, an exotic strain collected from Russia was assayed for its performance to suppress the growth of various seed-borne fungi of vegetable. The performance of the bio-agent was appraised based on growth suppression by dual culture method and reduction of seed-borne fungi in the bio-agent treated seeds. Ten seed samples comprise of summer and winter vegetables were examined collected from different local farmers. A total of fourteen fungal species belongs to twelve genera viz. Fusarium moniliforme, Botrytis cinerea, Aspergillus flavus, F. oxysporum, Botryodiplodia theobromae, Macrophomina phaseolina, A.niger, Cercospora sp., Phoma exigua, Rhizopus sp., Colletotrichum sp., Phytophthora sp., Penicillium sp., and Curvularia sp. were recorded from different untreated seeds. Vegetables seeds were treated in a concentration (10-3) of aqueous formulation of B. subtilis for two hours followed by air drying for 30 minutes. In general, the incidences of all fungal species of all kinds of vegetables seeds were reduced. But, selectively the best performances were observed in tomato, brinjal, cucumber, wax gourd and okra where most of the fungal species were completely suppressed by seed treatment with Bacillus subtilis. The growth of seed-borne fungi was inhibited highest in wax gourd (100%). The growth inhibition was also at satisfactory level in cucumber (95%), tomato (95%), brinjal (92%) and okra (86%) seeds. The findings of this research indicate the possibility of utilizing B. subtilis as seed treating agents instead of chemical fungicides to control seed-borne diseases of vegetables. J. Bangladesh Agril. Univ. 14(2): 177-184, December 2016